What is Neoschidium Mukherjee, Ambrose, Saha, and Bal, 2014 (Hemiptera: Reduviidae: Emesinae: Metapterini)? A reflection on taxonomic practices - Forero, Dimitri; Castro-Huertas, Valentina (Zootaxa, 2015)
Good taxonomic practice permits not only to adequately document the rapidly diminishing biodiversity of our planet (Wheeler 2008), but also let us set the foundations for phylogenetic assessments among groups of taxa, allowing a more deeply and proper understanding of the biota (Wheeler 2007). Therefore, any taxonomic problems will hinder not only phylogenetic approaches but conservation efforts as well (Dubois 2003; Mace 2004; Wheeler et al. 2012).